Citalopram and Tianeptine: Pharmacological Interventions in alcohol withdrawal-induced negative mood states and serotonin insufficiency in Albino Wistar male rats - Iffat Ara Amjad; Samina Bano Abdul Rub (Indonesian Journal of Pharmacy, 2019)
ABSTRACT  The present study aims to investigate the neurochemical and behavioural effects of tianeptine and citalopram to block alcohol withdrawal-induced audiogenic seizures in alcohol withdrawal (AW) rats. Citalopram and tianeptine were administered sub-chronically to block AW-induced audiogenic seizures. Brain regional tryptophan (TRP), 5-hydroxytryptamine (5-HT), 5-hydroxyindoleacetic acid (5-HIAA) concentrations were determined using high-performance liquid chromatography connected to the fluorimetric detector. Citalopram increased brain TRP concentration in all the regions, however, tianeptine increased brain TRP concentration only in amygdala and hippocampus. Increased brain serotonin concentration was seen by citalopram but not by tianeptine in all the regions. Further, tianeptine was shown to increase 5-HT turnover in all the regions, however, citalopram appeared to increase 5-HT turnover only in the hippocampus.  It is concluded that the citalopram and tianeptine behave differently on the intrinsic pathway of serotonin metabolism that appeared to be compensated by the release pattern of serotonin. Further, chronic exposure of serotonergic agents causes restoration and structural reforming of serotonin reuptake mechanism that is desensitized following chronic alcohol exposure. Thus the inclusive approach of the serotonergic system plays an undoubted role in the pharmacological management of AW syndrome.